Monovalent anion selective ion exchange membrane

By forming a specific distribution of anion and cation exchange polymer electrolytes in the porous polymer support, the problem of insufficient selectivity of monovalent anion-selective ion exchange membrane in the prior art is solved, and the penetration and application efficiency of high-selective monovalent anions are improved.

CN114423808BActive Publication Date: 2025-04-18TORAY ADVANCED MATERIALS KOREA INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202080065971.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-08-16
Filing Date
2020-08-18
Publication Date
2025-04-18
Estimated Expiration
2040-08-18

AI Technical Summary

Technical Problem

The prior art is difficult to develop highly selective monovalent anion-selective ion exchange membranes, resulting in inefficient application in fields such as electrodialysis, food processing and neutralization of wastewater.

Method used

By forming anion exchange polymer electrolyte in the central part of the porous polymer support and forming a cation exchange polymer electrolyte on the surface part, its content ratio is adjusted to achieve high selective penetration of monovalent anions.

Benefits of technology

High selective permeation of monovalent anions is achieved, which significantly reduces the exchange membrane permeability ratio of multivalent anions, thereby improving the selectivity and application efficiency of the ion exchange membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114423808B_ABST
    Figure CN114423808B_ABST
Patent Text Reader

Abstract

Disclosed is a monovalent anion selective ion exchange membrane and a method for preparing the ion exchange membrane. With respect to the structure of the monovalent anion selective ion exchange membrane, the content of the cation exchange polymer electrolyte in the surface portion is relatively high, the content of the anion exchange polymer electrolyte in the center portion is relatively high, and the content ratio of the anion exchange polymer electrolyte to the cation exchange polymer electrolyte increases continuously from the surface to the center in the thickness direction. Due to such a structure, the permeability of the multivalent anion exchange membrane is significantly reduced compared with the monovalent anion, so it can have high selectivity for the monovalent anion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a monovalent anion selective ion exchange membrane and a preparation method thereof. Background Art

[0002] Due to the worry about the exhaustion of fossil fuels such as oil and coal, and the problems such as global warming caused by the carbon dioxide produced by the use of fossil fuels, it is necessary to develop new energy sources that can replace fossil dyes. In this regard, various new renewable energy sources such as solar heat, biofuels, geothermal energy, wind power are currently developed and studied all over the world, but the ratio of this renewable energy source is still lower than 10% of global energy consumption. Moreover, for solar heat and wind power, which are studied as promising alternative energy sources for fossil fuels, their energy yield is very sensitive to the surrounding climate environment, so there are defects in the angle of ensuring stable energy yield. Therefore, the concern for environmentally friendly alternative energy sources that do not have the possibility of exhaustion and can stably produce energy is increasing.

[0003] As described environmental protection, replace energy source, use electrodialysis process to produce the process of high-purity salt, produce high-purity caustic soda and produce soft water in the process need univalent anion selective ion exchange membrane.In addition, in the fermentation process, food industry, pharmaceutical field, recovery acid and heavy metal and neutralization waste water that need univalent ion selectivity in the process of disengagement, also urgently need to develop ion exchange membrane with higher univalent ion selectivity.Therefore, in response to demand as mentioned above, actively carry out the research to univalent anion selective ion exchange membrane at present.But, the development of ion exchange membrane that only selectively sees through univalent anion with high ratio is in fact also insignificant.

[0004] Therefore, the present inventors discovered during the course of studying monovalent anion selective ion exchange membranes that an ion exchange membrane is prepared by forming an anion exchange polymer electrolyte in the central portion of a porous polymer support and a cation exchange polymer electrolyte in the surface portion, and that monovalent anions selectively permeate the ion exchange membrane at a higher ratio than polyvalent anions, thereby completing the present invention.

[0005] In this regard, Korean Patent Registration No. 10-1511990 discloses an ion exchange membrane for a reverse electrodialysis device and a reverse electrodialysis device including the same. Summary of the invention

[0006] Technical issues

[0007] The present invention is proposed to solve the above-mentioned problem. One embodiment of the present invention provides a monovalent anion selective ion exchange membrane.

[0008] Furthermore, another embodiment of the present invention provides a method for preparing a monovalent anion selective ion exchange membrane.

[0009] The technical problems to be solved by the present invention are not limited to the above-mentioned technical problems, and a person skilled in the art should clearly understand other technical problems not mentioned based on the following description.

[0010] Technical Solution

[0011] As a technical solution for achieving the above technical problem, one aspect of the present invention provides:

[0012] A monovalent anion selective ion exchange membrane, comprising a polymer support having a porous structure; and an ion exchange polymer electrolyte impregnated into the polymer support, wherein the ion exchange polymer electrolyte comprises an anion exchange polymer electrolyte and a cation exchange polymer electrolyte, the anion exchange polymer electrolyte is impregnated into the central portion of the polymer support, and the cation exchange polymer electrolyte is impregnated into the surface portion of the polymer support.

[0013] The content ratio of the anion exchange polymer electrolyte and the cation exchange polymer electrolyte may have the following relationship:

[0014] [Formula 1]

[0015] A≥B

[0016] Wherein, in Formula 1, A is the content ratio of anion exchange polymer electrolyte to cation exchange polymer electrolyte in the central part of the polymer support, B is the content ratio of anion exchange polymer electrolyte to cation exchange polymer electrolyte in the surface part of the polymer support, and the central part is a region with a depth of 20% to 80% from the surface to the center relative to 100% of the thickness of the polymer support, and the surface part is a region with a depth of 0% to 20% from the surface to the center relative to 100% of the thickness of the polymer support.

[0017] The content ratio of the anion exchange polymer electrolyte relative to the cation exchange polymer electrolyte may increase from the surface toward the center in the thickness direction of the polymer support.

[0018] The cation exchange polymer electrolyte may be contained in an amount of 10 parts by weight to 40 parts by weight relative to 100 parts by weight of the anion exchange polymer electrolyte.

[0019] The cation exchange polymer electrolyte may be obtained by cross-linking polymerization of a sulfonic acid-containing electrolyte monomer having an anionic group.

[0020] The sulfonic acid-containing electrolyte monomer having an anionic group may be selected from 2-acrylamide-2-methylpropanesulfonate sodium, vinylsulfonate sodium, vinylsulfonic acid, allyl sulfonate sodium, 2-methyl-2-propene-1-sulfonate sodium, 3-sulfopropyl acrylate sodium, and combinations thereof.

[0021] The anion exchange polymer electrolyte may be obtained by cross-linking polymerization of electrolyte monomers of quaternary ammonium salts having a cationic group.

[0022] The electrolyte monomer of the quaternary ammonium salt having a cationic group may be selected from (3-acrylamidopropyl)trimethylammonium chloride, (vinylbenzyl)trimethylammonium chloride, and a combination thereof.

[0023] The porous polymer support may have a void volume of 40% to 50%, a pore size of 0.07 μm to 0.1 μm, and a thickness of 8 μm to 30 μm.

[0024] The ratio of the thickness of the monovalent anion selective ion exchange membrane relative to the thickness of the polymer support may be 1.0 to 1.03.

[0025] And, according to another aspect of the present invention,

[0026] A method for preparing a monovalent anion selective ion exchange membrane is provided, which comprises: immersing a porous polymer support in an anion exchange precursor solution, wherein the anion exchange precursor solution comprises an electrolyte monomer having a cation, a crosslinking agent, an initiator and a solvent; irradiating the porous polymer support with light to form an anion exchange polymer electrolyte in the central portion of the porous polymer support by crosslinking the anion exchange precursor solution; immersing the porous polymer support having the anion exchange polymer electrolyte formed therein in a cation exchange precursor solution, wherein the cation exchange precursor solution comprises an electrolyte monomer having an anionic group, a crosslinking agent, an initiator and a solvent; and irradiating the porous polymer support immersed in the cation exchange precursor solution with light to form a cation exchange polymer electrolyte in the surface portion of the porous polymer support by crosslinking the cation exchange precursor solution.

[0027] The electrolyte monomer having a cationic group may be a quaternary ammonium salt electrolyte monomer.

[0028] The electrolyte monomer having an anionic group may be a sulfonic acid-containing electrolyte monomer.

[0029] Wherein, before being immersed in the anion exchange precursor solution, the porous polymer support may be hydrophilized by a surfactant.

[0030] The method for preparing the monovalent anion selective ion exchange membrane may further include: before forming the anion exchange polymer electrolyte, putting the upper membrane, the porous polymer support immersed in the anion exchange precursor solution, and the lower membrane into a pressing roller and pressing the upper membrane and the lower membrane onto the upper and lower parts of the polymer support, respectively; and after forming the anion exchange polymer electrolyte, removing the polymer support including the formed anion exchange polymer electrolyte, the upper membrane, and the lower membrane from the removal roller.

[0031] The method for preparing the monovalent anion selective ion exchange membrane may further include: before forming the cation exchange polymer electrolyte, putting the upper membrane, the porous polymer support immersed in the cation exchange precursor solution, and the lower membrane into a pressing roller and pressing the upper membrane and the lower membrane to the upper and lower parts of the polymer support respectively; and after forming the cation exchange polymer electrolyte, removing the polymer support, the upper membrane, and the lower membrane including the formed cation exchange polymer electrolyte from the removal roller.

[0032] Among the upper and lower films, one surface contacting the porous polymer support may be hydrophilically treated.

[0033] The pressing may be performed by a squeeze roller, and the sum of the thickness of the porous polymer support and the thickness of the film fed into the squeeze roller may have a value of 70% to 97% of the sum of the thicknesses before feeding into the squeeze roller.

[0034] Through the detachment, the cross-linked polymerized polymer resin formed outside the porous polymer support may be transferred to the upper and lower films to be removed.

[0035] Beneficial Effects

[0036] According to one embodiment of the present invention, the monovalent anion selective ion exchange membrane has the following structure: in the surface part, the content of the cation exchange polymer electrolyte is relatively high, in the central part, the content of the anion exchange polymer electrolyte is relatively high, and the content ratio of the anion exchange polymer electrolyte to the cation exchange polymer electrolyte increases continuously from the surface to the center in the thickness direction; therefore, the exchange membrane permeability of polyvalent anions is significantly reduced than that of monovalent anions, thereby having a higher selectivity for monovalent anions.

[0037] The advantageous effects of the present invention are not limited to the above-mentioned effects, but should be understood to include all effects that can be inferred based on the inventive constitution described in the detailed description of the present invention or the claims.

[0038] Brief description of the attached figure

[0039] Figure 1 FIG. 1 is a schematic diagram showing a monovalent anion selective ion exchange membrane according to an embodiment of the present invention.

[0040] Figure 2 It is a schematic diagram showing a method for preparing a monovalent anion selective ion exchange membrane according to one embodiment of the present invention.

[0041] Figure 3 Schematic diagram showing a roll-to-roll preparation process of a monovalent anion selective ion exchange membrane according to one embodiment of the present invention.

[0042] Figure 4 A mimetic diagram of a device for measuring the conductivity in a solution to calculate the membrane permeability of the monovalent anion selective ion exchange membrane according to an embodiment of the present invention and a comparative example is shown.

[0043] 5 is a graph showing the results of measuring concentration changes with respect to time changes in order to calculate the membrane permeability of the monovalent anion selective ion exchange membrane according to an embodiment of the present invention ( FIG. 5A ) and a comparative example ( FIG. 5B ). DETAILED DESCRIPTION

[0044] However, the present invention can be implemented in various forms and is not limited to the embodiments described in this specification, and is only defined according to the claims to be described later.

[0045] In addition, the terms used in the present invention are only used to describe specific embodiments and are not intended to limit the use of the present invention. Unless otherwise clearly defined in the context, expressions in the singular form also include expressions in the plural form. Unless otherwise stated to the contrary, throughout the specification of the present invention, "comprising" a component element means that other components may be further included, rather than excluding other components.

[0046] The first aspect of the present application

[0047] Provided is a monovalent anion selective ion exchange membrane, comprising a polymer support having a porous structure; and an ion exchange polymer electrolyte impregnated into the polymer support, wherein the ion exchange polymer electrolyte comprises an anion exchange polymer electrolyte and a cation exchange polymer electrolyte, the anion exchange polymer electrolyte is impregnated into the central portion of the polymer support, and the cation exchange polymer electrolyte is impregnated into the surface portion of the polymer support.

[0048] Below, refer to Figure 1 A monovalent anion selective ion exchange membrane according to a first aspect of the present invention is described.

[0049] According to one embodiment of the present application, Figure 1 To illustrate a schematic cross-sectional view of the monovalent anion selective ion exchange membrane 1, first, in this specification, the anion exchange polymer electrolyte 120 impregnated into the polymer support 110 is impregnated not only into the central portion but also partially into the surface portion, and the cation exchange polymer electrolyte 130 impregnated into the surface portion of the polymer support 110 should also be interpreted as being partially impregnated into the central portion, not only into the surface portion.

[0050] According to an embodiment of the present application, in the monovalent anion selective ion exchange membrane 1, the cation exchange polymer electrolyte 130 having an anion group is impregnated into the surface portion of the polymer support 110. Therefore, for polyvalent anions whose charge amount is relatively large compared to the monovalent anions, due to the strong repulsion with the anion group of the cation exchange polymer electrolyte 130 impregnated into the surface portion of the polymer support 110, the polyvalent anions may be relatively unlikely to permeate the cation exchange polymer electrolyte 130 compared to the monovalent anions. On the contrary, compared to the polyvalent anions, the monovalent anions having a smaller charge amount have a weaker repulsion with the cation exchange polymer electrolyte 130 having anion groups, and thus can relatively smoothly permeate the cation exchange polymer electrolyte 130 and can reach the anion exchange polymer electrolyte 120 impregnated into the central portion of the polymer support 110, and therefore, the monovalent anion selective ion exchange membrane 1 can selectively allow only the monovalent anions to permeate.

[0051] According to one embodiment of the present application, the content ratio of the anion exchange polymer electrolyte 120 and the cation exchange polymer electrolyte 130 may have the following relationship:

[0052] [Formula 1]

[0053] A≥B

[0054] In Formula 1, A is the content ratio of the anion exchange polymer electrolyte 120 to the cation exchange polymer electrolyte 130 in the central part of the polymer support 110, and B is the content ratio of the anion exchange polymer electrolyte 120 to the cation exchange polymer electrolyte 130 in the surface part of the polymer support 110, and the central part can be a region with a depth of 20% to 80% from the surface to the center relative to 100% of the thickness of the polymer support 110, and the surface part can be a region with a depth of 0% to 20% from the surface to the center relative to 100% of the thickness of the polymer support 110. In other words, the content of the anion exchange polymer electrolyte 120 may be equal to or greater than the content of the cation exchange polymer electrolyte 130 in a region of 20% to 80% depth in a direction from the surface to the center relative to 100% of the thickness of the polymer support 110, and the content of the cation exchange polymer electrolyte 130 may be equal to or greater than the content of the anion exchange polymer electrolyte 120 in a region of 0% to 20% depth in a direction from the surface to the center relative to 100% of the thickness of the polymer support 110. Therefore, it may not be excluded that both the anion exchange polymer electrolyte 120 and the cation exchange polymer electrolyte 130 are distributed in the entire region (central portion and surface portion) of the polymer support 110 but the anion exchange polymer electrolyte 120 and the cation exchange polymer electrolyte 130 have different content ratios.

[0055] According to an embodiment of the present application, the content ratio of the anion exchange polymer electrolyte 120 relative to the cation exchange polymer electrolyte 130 may increase from the surface to the center in the thickness direction of the polymer support 110. The content ratio of the anion exchange polymer electrolyte 120 relative to the cation exchange polymer electrolyte 130 may increase continuously or discontinuously from the surface to the center in the thickness direction of the polymer support 110. If it increases discontinuously, the content ratio of the anion exchange polymer electrolyte 120 relative to the cation exchange polymer electrolyte 130 may increase sharply at the interface between the surface portion and the center portion.

[0056] According to an embodiment of the present application, the content of the cation exchange polymer electrolyte 130 can be 10 to 40 parts by weight relative to 100 parts by weight of the anion exchange polymer electrolyte 120. When the content of the cation exchange polymer electrolyte 130 is less than 10 parts by weight, since multivalent anions can also permeate the monovalent anion selective ion exchange membrane 1, it is not possible to selectively allow monovalent anions to permeate; when the content of the cation exchange polymer electrolyte 130 is greater than 40 parts by weight, since there are too many anion groups in the cation exchange polymer electrolyte 130, monovalent anions may not be able to permeate the monovalent anion selective ion exchange membrane 1.

[0057] According to one embodiment of the present application, the anion exchange polymer electrolyte 120 may be obtained by cross-linking polymerization of an electrolyte monomer of a quaternary ammonium salt having a cationic group, and the electrolyte monomer of the quaternary ammonium salt may be represented by the following chemical formula 1:

[0058] [Chemical formula 1]

[0059]

[0060] In the chemical formula 1, R2 to R5 may be substituted or unsubstituted linear or side chain alkyl or aryl groups, and B may be a halogen.

[0061] According to one embodiment of the present application, the electrolyte monomer of the quaternary ammonium salt having a cationic group can be selected from (3-acrylamidopropyl)trimethylammonium chloride, (vinylbenzyl)trimethylammonium chloride and a combination thereof.

[0062] According to one embodiment of the present application, the cation exchange polymer electrolyte 130 may be obtained by cross-linking polymerization of a sulfonic acid electrolyte monomer having an anionic group, and the sulfonic acid electrolyte monomer having an anionic group may be represented by the following chemical formula 2:

[0063] [Chemical formula 2]

[0064]

[0065] In the chemical formula 2, R1 may be a substituted or unsubstituted straight chain or side chain alkyl or aryl group, and A may be hydrogen or a metal element.

[0066] According to one embodiment of the present application, the sulfonic acid-containing electrolyte monomer having an anionic group may be selected from 2-acrylamide-2-methylpropanesulfonate sodium, vinylsulfonate sodium, vinylsulfonic acid, 2-methyl-2-propene-1-sulfonate sodium, 3-sulfopropylacrylate sodium and combinations thereof.

[0067] According to one embodiment of the present application, the porous polymer support 110 is not particularly limited as long as it is a hydrocarbon-based polymer, and may include, for example, polyethylene, polypropylene, polyimide, polyamideimide, polypropylene oxide, polyethersulfone, polyurethane, and combinations thereof, but is not limited thereto.

[0068] According to an embodiment of the present application, the porous polymer support 110 may have a void volume of 40% to 50%, a pore size of 0.07 μm to 0.1 μm, and a thickness of 8 μm to 30 μm. In the case where the porous polymer support 110 does not meet the above characteristics, the anion exchange polymer electrolyte and the cation exchange polymer electrolyte will not be smoothly impregnated into the porous polymer support 110, and therefore, the monovalent anion selective ion exchange membrane 1 may not be easily prepared.

[0069] According to an embodiment of the present application, since the cross-linked polymer resin is removed from the outside of the porous polymer support 110, there may be no byproducts on the surface of the monovalent anion selective ion exchange membrane 1, and therefore, the monovalent anion selective ion exchange membrane 1 may have a smaller thickness. This characteristic may be achieved when the monovalent anion selective ion exchange membrane 1 is prepared by a roll-to-roll process, and this is described in detail in the second aspect of the present application described below.

[0070] According to one embodiment of the present application, the thickness ratio of the monovalent anion selective ion exchange membrane 1 to the polymer support 110 may be 1.0 to 1.03. Since the anion exchange polymer electrolyte 120 and the cation exchange polymer electrolyte 130 fill the inside of the polymer support, the thickness of the monovalent anion selective ion exchange membrane 1 may be equal to the thickness of the polymer support 110, or, as described later according to the second aspect of the present application, due to the surface roughness generated when the cation exchange electrolyte is removed from the surface, the thickness of the monovalent anion selective ion exchange membrane 1 is slightly greater than the thickness of the polymer support 110. In the case where the thickness ratio is greater than 1.03, the cation exchange polymer electrolyte 130 on the surface of the ion exchange membrane 1 may not be completely removed, which may serve as an obstacle to ion exchange. For example, more preferably, the thickness ratio may be 1.0 to 1.02.

[0071] The second aspect of the present application

[0072] A method for preparing a monovalent anion selective ion exchange membrane is provided, which comprises: immersing a porous polymer support in an anion exchange precursor solution, wherein the anion exchange precursor solution comprises an electrolyte monomer having a cation, a crosslinking agent, an initiator and a solvent; irradiating the porous polymer support with light to cause a crosslinking reaction on the anion exchange precursor solution to form an anion exchange polymer electrolyte in the central portion of the porous polymer support; immersing the porous polymer support having the anion exchange polymer electrolyte formed therein in a cation exchange precursor solution, wherein the cation exchange precursor solution comprises an electrolyte monomer having an anionic group, a crosslinking agent, an initiator and a solvent; and irradiating the porous polymer support immersed in the cation exchange precursor solution with light to cause a crosslinking reaction on the cation exchange precursor solution to form a cation exchange polymer electrolyte on the surface portion of the porous polymer support.

[0073] Although detailed description of the parts repeated in the first aspect of the present application is omitted, even if the description is omitted in the second aspect, the contents described in the first aspect of the present application can be applied to the second aspect in the same manner.

[0074] Below, refer to Figure 2 and Figure 3 , a method for preparing the monovalent anion selective ion exchange membrane according to the second aspect of the present application is described in detail according to the steps. Figure 2 Schematic diagram showing a method for preparing a monovalent anion selective ion exchange membrane according to one embodiment of the present invention, Figure 3 Schematic diagram showing a roll-to-roll preparation process of a monovalent anion selective ion exchange membrane according to one embodiment of the present invention.

[0075] First, according to one embodiment of the present application, the method for preparing the monovalent anion selective ion exchange membrane 1 includes immersing the porous polymer support 110 in an anion exchange precursor solution 700 (S100), wherein the anion exchange precursor solution 700 includes an electrolyte monomer having a cationic group, a cross-linking agent, an initiator and a solvent.

[0076] According to one embodiment of the present application, the electrolyte monomer having cations may be a quaternary ammonium salt electrolyte monomer, for example, may be selected from (3-acrylamidoproply)trimethylammonium chloride, (vinylbenzyl)trimethylammonium chloride, and combinations thereof.

[0077] According to one embodiment of the present application, the cross-linking agent may be an acrylamide cross-linking agent having a tertiary amine functional group, and may be represented by the following chemical formula 3:

[0078] [Chemical formula 3]

[0079]

[0080] In the chemical formula 3, R6 and R7 may be substituted or unsubstituted linear or side chain alkyl or aryl groups.

[0081] According to one embodiment of the present application, the acrylamide cross-linking agent having a tertiary amine functional group can be selected from N,N'bis(acryloyl)piperazine, N,N'-(1,2-dihydroxyethylene)bisacrylamide, N,N'-methylenebisacrylamide, N,N'-methylenebismethacrylamide and combinations thereof.

[0082] According to one embodiment of the present application, the cross-linking degree of the monovalent anion selective ion exchange membrane 1 to be prepared depends on the cross-linking agent, and the swelling degree and mechanical properties of the ion exchange membrane can be adjusted according to the content of the cross-linking agent.

[0083] According to one embodiment of the present application, the initiator may be a photoinitiator, for example, one of the Darocur or Irgacure series produced by CibaGeigy of Switzerland may be used, or 2-hydroxy-2-methyl-1-phenylpropane-1-one may be used.

[0084] According to one embodiment of the present application, the solvent may be a water-soluble solvent such as water, methanol, or ethanol. Preferably, the solvent may be water.

[0085] According to one embodiment of the present application, the electrolyte monomer with cations, the crosslinking agent, and the solvent can be mixed in a ratio of about 53 parts by weight to about 60 parts by weight: about 3 parts by weight to about 7 parts by weight: about 33 parts by weight to about 44 parts by weight, and the content of the initiator can be about 0.1 parts by weight to about 0.5 parts by weight relative to 100 parts by weight of the mixed solution of the electrolyte monomer with cations, the initiator, and the solvent. When the content of the electrolyte monomer with cations is less than the range, the ion exchange capacity that can improve the ion conductivity of the ion exchange membrane to be prepared may be insufficient, on the contrary, when the content exceeds the range, the durability of the ion exchange membrane to be prepared may be reduced. In addition, when the content of the crosslinking agent is less than the range, the insufficient degree of crosslinking may cause the durability of the ion exchange membrane to be prepared to be reduced, on the contrary, when the content exceeds the range, due to excessive crosslinking, the ion conductivity of the ion exchange membrane to be prepared may be significantly reduced. Moreover, when the content of the solvent is less than the range, the electrolyte monomer with a cationic group is impregnated too much into the porous polymer support, and therefore, the electrolyte monomer with an anionic group to be described later may be impregnated relatively less. Therefore, the thickness of the cationic exchange polymer electrolyte formed on the surface portion of the porous polymer support is reduced, resulting in that the ion exchange membrane to be prepared may not be able to achieve the effect of selectively exchanging monovalent anions. Moreover, when the content of the solvent is greater than the range, the electrolyte monomer with a cationic group is impregnated less into the porous polymer support, and therefore, the electrolyte monomer with an anionic group to be described later may be relatively impregnated too much into the porous polymer support. Therefore, the thickness of the cationic exchange polymer electrolyte formed on the surface portion of the porous polymer support increases, resulting in that the ion exchange membrane to be prepared may not be able to achieve the effect of selectively exchanging monovalent anions. That is, the content of the solvent may play a key role in the present invention in order to achieve the effect of selectively exchanging monovalent anions, specifically, the solvent evaporates during the cross-linking reaction and expands the pores on the surface of the porous polymer support. Therefore, when light is irradiated to the porous support immersed in the anion exchange precursor solution of the electrolyte monomer having a cationic group to perform a cross-linking reaction, the solvent in the anion exchange precursor solution is evaporated to expand the size of the pores formed in the surface portion of the porous support, and the cation exchange precursor solution is further immersed in the expanded pores to perform a cross-linking reaction, so that the anion exchange polymer electrolyte formed in the center portion and the cation exchange polymer electrolyte formed in the surface portion have an appropriate thickness in the porous polymer support.

[0086] According to one embodiment of the present application, the porous polymer support 110 may be hydrophilized by a surfactant before being immersed in the anion exchange precursor solution 700. At this time, the surfactant may be any material that can be hydrophilized, for example, dodecylbenzene sulfonic acid (DBSA), alkylbenzene sulfonic acid (ABS), linear alkylbenzenesulfonic acid (LAS), alphasulfonic acid (AS), alphaolefinsulfonic acid (AOS), fatty alcohol polyoxyethylene ether (AE), fatty alcohol polyoxyethylene ether sodium sulfate (AES) and combinations thereof, preferably, dodecylbenzenesulfonic acid. When the hydrophobic part of the surfactant is bound to the surface of the hydrophobic polymer support 110 through a hydrophobic-hydrophobic interaction, the hydrophilic part of the surfactant replaces the surface of the polymer support 110 to hydrophilize the surface of the surfactant. In this case, not only the outer surface of the polymer support 110 but also the entire inner pore surface of the polymer support 110 can be hydrophilized by the surfactant. Since the entire inner pore surface is hydrophilized, the hydrophilic anion exchange precursor solution 700 can be effectively and easily filled in the pores through a hydrophilic-hydrophilic interaction. Specifically, the hydrophilization treatment can be by the following method: the porous polymer support 110 is immersed in a solution obtained by diluting 0.5 wt% to 1 wt% of a commercially available surfactant with water for 1 to 2 minutes and then dried.

[0087] Next, according to one embodiment of the present application, the method for preparing the monovalent anion selective ion exchange membrane includes irradiating the porous polymer support 110 with light to cross-link the anion exchange precursor solution 700 to form an anion exchange polymer electrolyte 120 in the central portion of the porous polymer support 110 (S200).

[0088] According to an embodiment of the present application, Figure 3The roll-to-roll process shown in the figure performs the step S200. In this case, before step S200, it can further include putting the upper film 200, the porous polymer support 110 immersed in the anion exchange precursor solution 700, and the lower film 300 into a pressing roller to press the upper film 200 and the lower film 300 respectively on the upper and lower parts of the polymer support 110, and after step S200, it can further include removing the polymer support 110 including the formed anion exchange polymer electrolyte, the upper film 200, and the lower film 300 from the removal roller. At this time, the pressing roller can include an upper pressing roller 400 and a lower pressing roller 450 spaced apart from each other in the vertical direction, that is, two pressing rollers can be used, and the removal roller can also include an upper removal roller 500 and a lower removal roller 550 spaced apart from each other in the vertical direction, that is, two removal rollers can be used. The following describes in detail the case where the step S200 is performed according to a roll-to-roll process as an example, but this step is not limited to the roll-to-roll process.

[0089] According to an embodiment of the present application, the upper film 200 and the lower film 300 may include polyethylene terephthalate (PET).

[0090] According to an embodiment of the present application, the thickness of the upper film 200 and the lower film 300 may be about 30 μm to about 70 μm, preferably, about 50 μm to about 60 μm. In the case where the thickness of the upper film 200 and the lower film 300 is less than 30 μm, the porous polymer support 110 may be torn because the porous polymer support 110, the upper film 200 and the lower film 300 are not disassembled smoothly after the cross-linking reaction described later. In the case where the thickness of the upper film 200 and the lower film 300 is greater than 70 μm, when irradiating the light to be described later, the thickness of the film is too large, resulting in insufficient light irradiated to the porous polymer support 110, and therefore, the cross-linking reaction may not fully occur.

[0091] According to one embodiment of the present application, one surface of the upper film 200 and the lower film 300 that contacts the porous polymer support 110 may be untreated or hydrophilic. The hydrophilic treatment may be, for example, hydrophilic treatment with silicone, polyvinyl alcohol, polyallylamine hydrochloride, polyvinylamine, polystyrene sulfonic acid, polyethylene sulfonic acid, etc. Preferably, hydrophilic treatment may be performed with silicone. That is, by performing hydrophilic treatment on one surface of the upper film 200 and the lower film 300 that contacts the porous polymer support 110, it is possible to promote the combination with the porous polymer support 110 hydrophilized by a surfactant.

[0092] According to one embodiment of the present application, the pressing can be performed by extrusion to obtain a value less than the sum of the thickness of the porous polymer support 110 put into the pressing roller and the thickness of the upper film 200 and the lower film 300. 2 To about 100kgf / cm 2 That is, by performing the extrusion to more strongly bond the porous polymer support 110 and the upper film 200 and the lower film 300, as will be described later, the cross-linked polymer resin 710 formed outside the porous polymer support 110 can be more easily transferred to the upper film 200 and the lower film 300 to be removed.

[0093] According to an embodiment of the present application, by the extrusion, the sum of the thickness of the porous polymer support and the film thickness put into the pressing roller may have a value of 70% to 97% of the sum of the thicknesses before the putting. When the value is less than 70%, the porous polymer support 110 and the upper film 200 and the lower film 300 may not be easily disassembled in the subsequent disassembly step. When the value is greater than 90%, the cross-linked coupled polymer resin 710 formed outside the porous polymer support 110 may not be easily transferred to the upper film 200 and the lower film 300 in the subsequent disassembly step, and therefore may not be removed.

[0094] According to an embodiment of the present application, the speed at which the upper film 200, the porous polymer support 110 and the lower film 300 are put into the pressing roller can be about 0.5 m / min to about 2 m / min. When the speed is lower than 0.5 m / min, the production efficiency may be reduced due to the slow process speed. When the speed is higher than 2 m / min, due to the high process speed, the cross-linking reaction of the anion exchange precursor solution 700 may not be smoothly carried out in the subsequent process.

[0095] According to an embodiment of the present application, the cross-linking reaction of the anion exchange precursor solution 700 may be performed by irradiating light to the porous polymer support 110 on which the upper film 200 and the lower film 300 are pressed. At this time, the irradiation of the light may be performed on both the upper and lower parts of the porous polymer support 110 on which the upper film 200 and the lower film 300 are pressed.

[0096] According to an embodiment of the present application, the irradiated light may be ultraviolet light, the types of ultraviolet light may be divided into UVA, UVB and UVV, and the ultraviolet light may have different wavelengths. Specifically, UVA may have a wavelength of about 320 nm to about 400 nm, UVB may have a wavelength of about 280 nm to about 320 nm, and UVV may have a wavelength of about 400 nm to about 450 nm.

[0097] According to an embodiment of the present application, the energy of the irradiated ultraviolet rays may be about 40 mW / cm 2 to about 50mW / cm 2 , UVB can be about 30mW / cm 2 to about 50mW / cm 2 , and UVV can be about 30mW / cm 2 to about 50mW / cm 2 , preferably, UVA can be about 47mW / cm 2 , UVB can be about 37mW / cm 2 , and UVV can be about 35mW / cm 2 When the energy of the irradiated ultraviolet light is less than the above range, the cross-linking reaction of the anion exchange precursor solution 700 may not be smooth. When the energy of the irradiated ultraviolet light exceeds the above range, the porous polymer support 110, the upper film 200 and the lower film 300 may be carbonized due to the excessive energy.

[0098] According to an embodiment of the present application, the ultraviolet rays may be irradiated for the following time: UVA for about 360 seconds to about 480 seconds, UVB for about 360 seconds to about 480 seconds, and UVV for about 360 seconds to about 480 seconds. When the ultraviolet rays are irradiated for a time shorter than the range, the cross-linking reaction of the anion exchange precursor solution 700 may not be smoothly performed. When the ultraviolet rays are irradiated for a time longer than the range, the porous polymer support 110, the upper film 200, and the lower film 300 may be carbonized.

[0099] According to an embodiment of the present application, after the anion exchange polymer electrolyte 120 is formed as described above, step S200 further includes removing the polymer support 110 including the formed anion exchange polymer electrolyte 120 , the upper film 200 , and the lower film 300 from a removal roller.

[0100] According to an embodiment of the present application, through the disassembly, the cross-linked polymer resin 710 formed on the outside of the porous polymer support 110 may be transferred to the upper film 200 and the lower film 300 to be removed.

[0101] According to one embodiment of the present application, the interval between the upper detachment roller 500 and the lower detachment roller 550 may be the same as the sum of the thicknesses of the porous polymer support 110, the upper film 200, and the lower film 300 before being put into the pressing roller. At this time, the porous polymer support 110 before being put into the pressing roller refers to the polymer support 110 before being immersed in the anion exchange precursor solution 700. That is, the thickness of the porous polymer support 110 may be the thickness of the polymer support 110 excluding the anion exchange precursor solution 700.

[0102] According to one embodiment of the present application, the disassembly is achieved by pulling the upper film 200 and the lower film 300 through the disassembly roller at different sides. At this time, the directions of the different sides can be the diagonal directions of the upper disassembly roller 500 and the lower disassembly roller 550, respectively.

[0103] Next, according to one embodiment of the present application, the method for preparing the monovalent anion selective ion exchange membrane 1 includes immersing the porous polymer support 110 having the anion exchange polymer electrolyte 120 formed therein in a cation exchange precursor solution 700 including an electrolyte monomer having an anionic group, a cross-linking agent, an initiator and a solvent (S300).

[0104] According to one embodiment of the present application, the electrolyte monomer having an anionic group may be a sulfonic acid-containing electrolyte monomer, for example, may be selected from 2-acrylamide-2-methylpropanesulfonate sodium, vinylsulfonate sodium, vinylsulfonic acid, allylsulfonate sodium, 2-methyl-2-propene-1-sulfonate sodium, 3-sulfopropylacrylate sodium and combinations thereof.

[0105] According to an embodiment of the present application, the cross-linking agent and the initiator may be the same as the cross-linking agent and the initiator used in the step S100.

[0106] According to one embodiment of the present application, the cation exchange precursor solution 700 may be a mixture of about 44 parts by weight to about 47 parts by weight of the electrolyte monomer having an anionic group, about 6 parts by weight to about 12 parts by weight of the crosslinking agent, and about 44 parts by weight to about 47 parts by weight of the solvent, and the content of the initiator may be about 0.1 parts by weight to about 0.5 parts by weight relative to 100 parts by weight of the solution obtained by mixing the electrolyte monomer having an anionic group, the crosslinking agent and the solvent. When the content of the electrolyte monomer having an anionic group is less than the range, the ion exchange capacity capable of submitting the ion conductivity of the prepared ion exchange membrane 1 may be insufficient, on the contrary, when the content exceeds the range, the durability of the prepared ion exchange membrane 1 may be reduced. In addition, when the content of the crosslinking agent is less than the range, the insufficient crosslinking degree may cause the durability of the prepared ion exchange membrane 1 to be reduced, on the contrary, when the content exceeds the range, the ion conductivity of the prepared ion exchange membrane 1 may be significantly reduced.

[0107] Next, according to one embodiment of the present application, the method for preparing the monovalent anion selective ion exchange membrane includes irradiating light to a porous polymer support immersed in the cation exchange precursor solution and cross-linking the cation exchange precursor solution to form a cation exchange polymer electrolyte on the surface portion of the porous polymer support (S400).

[0108] According to an embodiment of the present application, as in step S200, step S400 is performed by Figure 3 Since the entire description is performed with the process, the subsequent processes are the same as the above description, so they are not repeated here.

[0109] According to an embodiment of the present application, the content of the cation exchange polymer electrolyte 130 can be 10 to 40 parts by weight relative to 100 parts by weight of the anion exchange polymer electrolyte 120. When the content of the cation exchange polymer electrolyte 130 is less than 10 parts by weight, since multivalent anions can also permeate the monovalent anion selective ion exchange membrane 1, it is not possible to selectively allow monovalent anions to permeate; when the content of the cation exchange polymer electrolyte 130 is greater than 40 parts by weight, since there are too many anion groups in the cation exchange polymer electrolyte 130, monovalent anions may not be able to permeate the monovalent anion selective ion exchange membrane 1.

[0110] According to one embodiment of the present application, in the prepared monovalent anion selective ion exchange membrane 1 , the cation exchange polymer electrolyte 130 may not be formed outside the polymer support 110 , and the porous structure of the polymer support 110 is exposed on the surface of the monovalent anion selective ion exchange membrane 1 .

[0111] According to one embodiment of the present application, the cation exchange polymer electrolyte 130 is not formed outside the polymer support 110, which should be interpreted as including that it can be formed on at least a portion of the outside of the polymer support 110. In addition, the porous structure of the polymer support 110 is exposed on the surface of the monovalent anion selective ion exchange membrane 1, which should be interpreted as including that at least a portion of the porous structure of the polymer support 110 can be exposed, and should be interpreted as exposing the porous structure of the surface of the polymer support 110.

[0112] According to an embodiment of the present application, since the cross-linked polymer resin formed on the outside of the porous conjugate support 110 is removed, the monovalent anion selective ion exchange membrane 1 has no by-products on its surface and can have a smaller thickness.

[0113] According to one embodiment of the present application, the weight ratio of the polymer support 110 and the ion exchange polymer electrolyte (the anion exchange polymer electrolyte 120 and the cation exchange polymer electrolyte 130) can be 1:0.8 to 1:1.1. In the case where the weight ratio of the ion exchange polymer electrolyte filled in the polymer support 110 is lower than 1:0.8, it may be difficult to exhibit the physical and electrochemical properties of the ion exchange membrane to be realized due to insufficient filling content of the ion exchange polymer electrolyte. On the contrary, in the case where the weight ratio is higher than 1:1.1, it may be difficult to form a uniform ion exchange membrane due to the polymer electrolyte remaining on the surface of the monovalent anion selective ion exchange membrane 1.

[0114] Hereinafter, embodiments of the present invention are described in detail for easy implementation by those skilled in the art. However, the present invention can be embodied in various forms and is not limited to the embodiments described herein.

[0115] <Example> Preparation of monovalent anion selective ion exchange membrane

[0116] 1. Filling with anion exchange polymer electrolyte

[0117] A polymerization solution was prepared by mixing (vinylbenzyl)trimethylammonium chloride (99%), 1,4-acryloylpiperizine, and water in a weight ratio of 12:1:9, and an initiator solution of 0.01 weight ratio of N,N'-azobisisobutyronitrile diluted in methanol in a weight ratio of 10 was used. Then, a porous polyethylene support with a thickness of 16 μm and a pore distribution of 45% was immersed in the mixed solution so that the monomer could fully penetrate the support, and the porous polyethylene support was placed between polyethylene terephthalate (PET) films, and irradiated with about 47 mW / cm for UVA. 2 The intensity of ultraviolet rays is about 37mW / cm for UVB 2 The intensity of ultraviolet light is about 35mW / cm for UVV 2 After the cross-linking process, the PET film and the by-products attached to the surface of the support are removed to obtain an anion exchange membrane for the first time.

[0118] 2. Filling with cation exchange polymer electrolyte

[0119] In order to fill the cation exchange polymer electrolyte on both sides of the anion exchange membrane prepared by the anion exchange polymer electrolyte filling described in 1., the anion exchange membrane prepared by the above-mentioned 1. is immersed in a solution obtained by mixing acrylamide-2-methyl-1-propanesulfonic acid (acrylamide-2-methyl-1-propanesulfonic acid, 99%), 1,4-acryloylpiperazine, and water in a weight ratio of 12:1:12, so that the solution can fully penetrate through the pores that are not completely filled in the surface of the anion exchange membrane prepared by the above 1., and then, the anion exchange membrane is irradiated with about 47 mW / cm2 for UVA through a polyethylene terephthalate (PET) film. 2 The intensity of ultraviolet rays is about 37mW / cm for UVB 2 The intensity of ultraviolet light is about 35mW / cm for UVV 2 After the cross-linking reaction was performed by ultraviolet light of high intensity, the PET film and the by-products attached to the surface of the support were removed to obtain a monovalent selective anion exchange membrane.

[0120] <Comparative Example> Preparation of a commercial anion-exchange membrane (AMV)

[0121] A commercially available monovalent anion exchange membrane (Asahi Glass, Japan) was used for comparison with the examples.

[0122] <Test example>

[0123] The ion exchange membranes according to the examples and comparative examples were installed in Figure 4 The measuring device shown in the figure, then, a 1 normal concentration (1N) sodium chloride, sodium nitrate, sodium carbonate or sodium sulfate aqueous solution is placed in a container on the left side of the membrane, and distilled water is placed in a container on the right side of the membrane. The conductivity is measured for 2 hours to determine the amount of ions in the aqueous solution that permeate through the membrane sample over time. The results obtained by measuring the conductivity according to the concentration of each solution are converted into concentrations, and the concentration changes over time are shown in FIG5. FIG5A is a chart showing the result data using the ion exchange membrane according to the embodiment, and FIG5B is a chart showing the result data using the ion exchange membrane according to the comparative example.

[0124] And, the membrane permeability P to ion crossing will be calculated by the following formula: crossover The results are shown in Table 1 below.

[0125]

[0126] (Wherein, in the formula, V is the volume (cm) of the solution of the same content supplied to both sides (the side containing the corresponding ions and the side containing pure water) of the permeability measurement cell. 3 ), L is the thickness of the ion exchange membrane used to measure the permeability (cm), A is the effective area of ​​the ion exchange membrane used to measure the permeability (cm 2 ), C A is the initial ion concentration (M) in the solution containing the corresponding ion, C B (t) is the concentration of the corresponding ion that crosses to the pure water side and changes with time (M), t is the time of change at the measurement time point (s), and t0 is the initial time before measurement (s))

[0127]

Table 1

[0128]

[0129] According to FIG. 5 and Table 1, it can be confirmed that, unlike the commercially available monovalent anion selective ion exchange membrane according to the comparative example, in the monovalent anion selective ion exchange membrane according to the embodiment of the present application, the monovalent anion (Cl - 、NO3 - ) is significantly higher than the divalent anion (CO3 2- and SO4 2- ) permeability, and therefore, the selectivity for monovalent anions is significantly superior to that of the anion exchange membrane according to the comparative example.

Claims

1. A monovalent anion selective ion exchange membrane comprising: A polymer support having a porous structure; as well as an ion exchange polymer electrolyte impregnated in the polymer support, in, The ion exchange polymer electrolyte includes an anion exchange polymer electrolyte and a cation exchange polymer electrolyte. An anion exchange polymer electrolyte is impregnated into the central portion of the polymer support, A cation exchange polymer electrolyte is impregnated into the surface portion of the polymer support, and In the thickness direction of the polymer support, the content ratio of the anion exchange polymer electrolyte to the cation exchange polymer electrolyte continuously increases from the surface of the polymer support toward the center of the polymer support.

2. The monovalent anion selective ion exchange membrane according to claim 1, in, The content ratio between the anion exchange polymer electrolyte and the cation exchange polymer electrolyte has the following relationship: [Formula 1] A ≥ B Wherein, in the formula 1, A is the content ratio of the anion exchange polymer electrolyte to the cation exchange polymer electrolyte in the central part of the polymer support, B is the content ratio of the anion exchange polymer electrolyte to the cation exchange polymer electrolyte on the surface of the polymer support, The central portion is a region having a depth of 20% to 80% in a direction from the surface of the polymer support toward the center of the polymer support relative to 100% thickness of the polymer support, and, The surface portion is a region having a depth of 0% to 20% in a direction from the surface of the polymer support toward the center of the polymer support relative to 100% thickness of the polymer support.

3. The monovalent anion selective ion exchange membrane according to claim 1, in, The content of the cation exchange polymer electrolyte is 10 parts by weight to 40 parts by weight relative to 100 parts by weight of the anion exchange polymer electrolyte.

4. The monovalent anion selective ion exchange membrane according to claim 1, in, The cation exchange polymer electrolyte is obtained by cross-linking polymerization of sulfonic acid-containing electrolyte monomers having anionic groups.

5. The monovalent anion selective ion exchange membrane according to claim 4, in, The sulfonic acid electrolyte monomer having an anionic group is selected from sodium 2-acrylamide-2-methylpropane sulfonate, sodium vinyl sulfonate, vinyl sulfonic acid, sodium allyl sulfonate, sodium 2-methyl-2-propene-1-sulfonate, sodium 3-sulfopropyl acrylate and combinations thereof.

6. The monovalent anion selective ion exchange membrane according to claim 1, in, The anion exchange polymer electrolyte is obtained by cross-linking polymerization of electrolyte monomers of quaternary ammonium salts having cationic groups.

7. The monovalent anion selective ion exchange membrane according to claim 6, in, The electrolyte monomer of the quaternary ammonium salt having a cationic group is selected from (3-acrylamidopropyl)trimethylammonium chloride, (vinylbenzyl)trimethylammonium chloride and a combination thereof.

8. The monovalent anion selective ion exchange membrane according to claim 1, in, The porous polymer support has a void volume of 40% to 50%, a pore size of 0.07 μm to 0.1 μm, and a thickness of 8 μm to 30 μm.

9. The monovalent anion selective ion exchange membrane according to claim 1, in, The ratio of the thickness of the monovalent anion selective ion exchange membrane relative to the polymer support is 1.0 to 1.

03.

10. A method for preparing the monovalent anion selective ion exchange membrane according to claim 1, comprising: Immersing the porous polymer support in an anion exchange precursor solution, wherein the anion exchange precursor solution comprises an electrolyte monomer having a cationic group, a crosslinking agent, an initiator, and a solvent; Putting the upper membrane, the porous polymer support immersed in the anion exchange precursor solution and the lower membrane into a pressing roller and pressing the upper membrane and the lower membrane onto the upper and lower parts of the polymer support respectively; forming an anion exchange polymer electrolyte in the central portion of the porous polymer support by irradiating light to the porous polymer support to cross-link the anion exchange precursor solution; removing the polymer support including the formed anion exchange polymer electrolyte, the upper membrane, and the lower membrane from a removal roll; Immersing the porous polymer support having the anion exchange polymer electrolyte formed therein in a cation exchange precursor solution, wherein the cation exchange precursor solution comprises an electrolyte monomer having an anion group, a crosslinking agent, an initiator, and a solvent; Putting the upper membrane, the porous polymer support immersed in the cation exchange precursor solution and the lower membrane into a pressing roller and pressing the upper membrane and the lower membrane onto the upper and lower parts of the polymer support respectively; irradiating light to the porous polymer support immersed in the cation exchange precursor solution to cross-link the cation exchange precursor solution to form a cation exchange polymer electrolyte on a surface portion of the porous polymer support; and The polymer support including the formed cation exchange polymer electrolyte, the upper film, and the lower film are detached from the detachment roll.

11. The method for preparing a monovalent anion selective ion exchange membrane according to claim 10, in, The electrolyte monomer having a cationic group is a quaternary ammonium salt electrolyte monomer.

12. The method for preparing a monovalent anion selective ion exchange membrane according to claim 10, in, The electrolyte monomer having an anionic group is an electrolyte monomer containing sulfonic acid.

13. The method for preparing a monovalent anion selective ion exchange membrane according to claim 10, in, Before being immersed in the anion exchange precursor solution, the porous polymer support is hydrophilized by a surfactant.

Citation Information

Patent Citations

  • Polymer functional film, stack or device provided with polymer functional film, and method of producing polymer functional film

    CN106574062A